TORSIONAL VIBRATION ANALYSIS AND PARAMETER OPTIMIZATION OF AUTOMOBILE POWER TRANSMISSION SYSTEM BASED ON AMESIM - LIU Fang; DONG XiaoChen; ZHANG YaZhen; HAN Jie (Jixie qiangdu)
In order to study the torsional vibration problem of the transmission system of a front-rear-drive MPV model, a 21-degree-of-freedom transmission system torsional vibration equivalent model was established based on AMEsim software, and the torsional vibration analysis of the established model was carried out through free vibration calculation and forced vibration calculation. The torsional vibration test of the vehicle transmission system is carried out, the simulation results are compared with the experimental results, and the accuracy of the simulation model is verified in two aspects: Modal frequency and torsional vibration response. Based on the established vehicle transmission system model, the moment of inertia, torsional stiffness and damping in the model are analyzed through sensitivity analysis. The conclusions obtained show that the six system parameters have a greater impact on the transmission system.The multi-parameter adjustment based on MATLAB genetic algorithm is adopted for these parameters. After adjustment, the torsion amplitude values at the transmission and final reducer are reduced by 20.16% and 23% respectively, which greatly reduces the torsion amplitude of the transmission system.